Colonization dynamics of arbuscular mycorrhizal fungi (AMF) in Ilex paraguariensis crops: Seasonality and influence of management practices - Velázquez, María Silvana (2018)
The yerba mate (Ilex paraguariensis St. Hill.) is a native species from subtropical regions of Argentina, Brazil, Paraguay and Uruguay. Arbuscular mycorrhizal fungi (AMF) are symbiotically associated with 82% of the vegetable species including crops of economic importance. The aim of the present study was to determine the association of yerba mate with AMF growing in natural and crop conditions, and to evaluate the influence of tillage practices and seasonality on root colonization. We selected five situations ranging from old systems to recent implementations with different agricultural managements and intensity of tillage, as reference native trees were analyzed. Root samples of yerba mate were extracted in winter and summer during the years 2013–2014. The percentage of root colonization was determined. Significantly higher values of colonization were found in native trees. Regarding seasonality, significantly higher values on the total mycorrhizal colonization were observed in winter. Organic matter and nitrogen were the soil factors that showed significant correlation with the percentage of colonization. This work confirms the association of I. paraguariensis with AMF, showing that yerba mate is a host species under both crop and natural conditions. Even though crop management of yerba mate is compatible with the symbiosis, it affects the colonization negatively.